Cold sensor, hot topic: TRPM8 plays a role in monocyte function and differentiation. Issue 3 (15th May 2022) - Trusiano, Brie; Tupik, Juselyn D.; Allen, Irving C.
Abstract: Understanding the innate immune system and how aberrant activation or impaired inhibition leads to the development of hyperinflammatory conditions, including inflammatory bowel disease, is crucial for patient management and treatment. An emerging area of interest surrounding dysregulated inflammation focuses on membrane bound transient receptor potential (TRP) ion channels. These channels are permeable to calcium and other cations involved in the balance of leukocyte membrane potential and function, as well as afferent neuron signaling within the myenteric plexus of the GI tract, bladder, and skin. A particular channel, TRPM8, is an important cell surface marker for prostate cancer and participates in the function of cold sensing neurons. Specifically, this ion‐gated receptor is shown to be activated by agonists such as menthol and eucalyptus, which aid in the soothing, cooling effects of these agents. Furthermore, the TRPM8 channel is also identified on the surface of resident tissue Mϕs and is also linked to the protective role and release of calcitonin gene‐related peptide (CGRP) by sensory neurons. Graphical Abstract: Discussion on TRPM8 function in monocyte differentiation and disease emphasizes the need for future characterization of cation channel mechanisms.